Biofortified rice - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
Rice is the dominant cereal crop in many developing countries and is the staple food for more than half of the world’s population. In several Asian countries, rice provides 50–80 percent of the energy intake of the poor. Because of the high per capita consumption of rice in these countries, increasing its nutritive value could have significant positive health outcomes for millions of people... Breeding programs aimed at producing varieties with high iron and zinc concentrations also seek to combine the high mineral content with other seed and food characteristics attractive to farmers or consumers. Studies by HarvestPlus and others have shown considerable losses of iron and zinc during the polishing of rice. For this reason, HarvestPlus breeding work is focused on increasing mineral levels in white rice.